Mechanical properties and fracture surface roughness of thermally damaged granite under dynamic splitting - Yijin Qian; Peng Jia; Songze Mao; Jialiang Lu (Deep Underground Science and Engineering, 2024)
Abstract In order to understand the mechanical properties and the fracture surface roughness characteristics of thermally damaged granite under dynamic splitting, dynamic Brazilian splitting tests were conducted on granite samples after thermal treatment at 25, 200, 400, and 600°C. Results show that the dynamic peak splitting strength of thermally damaged granite samples increases with increasing strain rate, showing obvious strain‐rate sensitivity. With increasing temperature, thermally induced cracks in granite transform from intergranular cracks to intragranular cracks, and to a transgranular crack network. Thermally induced damages reduce the dynamic peak splitting strength and the maximum absorbed energy while increasing the peak radial strain. The fracture mode of the thermally damaged granite under dynamic loads is mode II splitting failure. By using the axial roughness index Z 2 a, the distribution ranges of the wedge‐shaped failure zones and the tensile failure zones in the fracture surfaces under dynamic Brazilian splitting can be effectively identified. The radial roughness index Z 2 r is sensitive to the strain rate and temperature. It shows a linear correlation with the peak splitting strength and the maximum absorbed energy and a linear negative correlation with the peak radial strain. Z 2 r can be used to quantitatively estimate the dynamic parameters based on the models proposed.